Functional Characterization Of The Outer Membrane Protein TolC of Salmonella enterica subspecies enterica serovar Typhi And Its Association With Virulence - Hussain, Ashraf (2018)
Although Salmonella enterica subspecies enterica serovar Typhi (S. Typhi) has been well studied, only a few of its outer membrane proteins (OMPs) have been functionally characterized. In this study, a tolC deletion mutant was generated to study the biological functions of TolC in S. Typhi strain that was isolated from an acute typhoid patient. Deletion of TolC caused increase susceptibility to a range of antimicrobials challenge, compromised membrane integrity, and reduced efflux activity of S. Typhi. In addition, the ΔtolC mutant was shown to have lower adhesion and invasion capability in an in vitro human cell culture infection model.